The Impact of Profitability and Leverage on The Timeframe of Financial Statement Publication - Pande Putu Maha Gayatri Putri; Made Gede Wirakusuma (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2025)
The timeframe of financial statement publication refers to the interval between the end of the financial reporting period and the date the report is made available to the public. Prompt and timely publication of financial statements reduces information asymmetry between agents and principals. This study aims to provide empirical evidence on the effect of profitability and leverage on the timeframe of financial statement publication. The research was conducted on all companies listed on the Indonesia Stock Exchange (IDX) during the 2023 period. Industry type was used as a control variable. The sample was determined using a non-probability sampling method with a purposive sampling technique, resulting in 788 observations. The data were analyzed using multiple linear regression. The results show that profitability has a negative effect on the timeframe of financial statement publication, while leverage has no significant effect